Effectiveness of molnupiravir for treating COVID-19 in patients with psychiatric disorders - Liu, Ting-Hui; Liao, Hsuan-Yi; Chang, Chih-Cheng; Lai, Chih-Cheng (Frontiers in Pharmacology, 2024)
Objectives This study investigated the clinical effectiveness of molnupiravir for treating non-hospitalized COVID-19 patients with pre-existing psychiatric disorder. Methods This retrospective cohort study used the TriNetX research network to identify patients with psychiatric disorder who experienced non-hospitalized COVID-19 between 1 January 2022, and 1 May 2023. The propensity score matching (PSM) method was used to match patients receiving molnupiravir (treated group) with those who did not (untreated group). The outcome included short-term outcomes - the composite of all-cause hospitalization or death within 30 days and the risk of post-COVID-19 conditions up to a year after COVID-19 diagnosis. Results Two groups of 9,421 patients, each with balanced baseline characteristics, were identified using the PSM method. During the 30-day follow-up, treated group was associated with a reduced risk of hospitalization or mortality compared to untreated group (HR, 0.760; 95% CI, 0.665–0.869). Compared to untreated group, treated group also exhibited a decreased risk of experiencing post-COVID-19 conditions, including chest/throat pain (HR, 0.615; 95% CI, 0.543–0.696), abnormal breathing (HR, 0.761; 95% CI, 0.687–0.884), abdominal symptoms (HR, 0.748; 95% CI, 0.674–0.831), fatigue (HR, 0.718; 95% CI, 0.638–0.808), headache (HR, 0.753; 95% CI, 0.665–0.852), cognitive symptoms (HR, 0.769; 95% CI, 0.630–0.940), myalgia (HR, 0.647; 95% CI, 0.530–0.789), cough (HR, 0.867; 95% CI, 0.770–0.978), and palpitation (HR, 0.641; 95% CI, 0.534–0.770) during the 1-year follow-up. Conclusion Molnupiravir could be associated with lower rates of all-cause hospitalization or death and also lower risk of post-COVID-19 condition among non-hospitalized COVID-19 patients with pre-existing psychiatric disorder.